ANALISIS SAMBUNGAN BAUT BALOK KOLOM RANGKA BAJA STRUKTURAL DENGAN PROFIL IWF MENGGUNAKAN PROGRAM BANTU ELEMEN HINGGA - Machmud Budi Sulistiyo; Gati Annisa Hayu; Entin Hidayah (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
Commonly joints problems (especially high strength bolt) were stiffness, ductility, and construction costs. This research was conducted with purpose to analyzed inner force and behavior that could be occurred on high strength bolted joints in steel frame using IWF profiles, such as stress, and reaction force-displacement. This study was divided into 2 step, first step was modeling on finite element software, and second step was analyzing the results and comparing it with the results from experimental study as validation base. In bolted joints model showed the best value on third trial with displacement value of 98,97 mm and reaction force of 41,57 KN. With validation to experimental results each one were 93,45% and 94,05%. Accuracy of hysteretic loop curve area was 98,46%.